2020
DOI: 10.1177/0020852319899433
|View full text |Cite
|
Sign up to set email alerts
|

Blaming the bureaucrat: does perceived blame risk influence inspectors’ enforcement style?

Abstract: Is there a relation between street-level bureaucrats’ enforcement style and their perception of the risk of getting blamed? This article answers this question on the basis of a survey ( n = 507) among inspectors of the Netherlands Food and Product Safety Authority. We included perceived media attention on their work as a factor that might influence street-level bureaucrats’ perception of blame risk and their enforcement style. Three dimensions of enforcement style were distinguished from earlier research: lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tepe and Prokop (2018) show that public administration students report higher levels of subjective risk aversion but do not behave in a more risk-averse way in a compound lottery choice experiment. Klijn et al (2020: 5) show that street-level bureaucrats’ enforcement style is affected by the risk of being blamed for poor performance. They found that when inspectors perceive more blame risk, they act less formally and less coercively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Tepe and Prokop (2018) show that public administration students report higher levels of subjective risk aversion but do not behave in a more risk-averse way in a compound lottery choice experiment. Klijn et al (2020: 5) show that street-level bureaucrats’ enforcement style is affected by the risk of being blamed for poor performance. They found that when inspectors perceive more blame risk, they act less formally and less coercively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Enforcement style was measured using the three-dimensional validated scale by de Boer ( 2019) with a 10-point answer scale. This scale is developed building on the classic work of, amongst others, Winter (1999, 2000) and has already been empirically applied to study explanations of enforcement style (see de Boer, Eshuis, and Klijn 2018;Klijn et al 2020). The three dimensions of enforcement style (i.e.…”
Section: Enforcement Stylementioning
confidence: 99%